Occupational Safety, Health, and Well-being Among Home-based Workers in the Informal Economy of Thailand - Nankongnab, Noppanun (New Solut, 2015)
The objective of this article is to provide a summary of the issues related to occupational safety and health and well-being among workers in the informal economy of Thailand, with a special emphasis on home-based workers. The reviewed literature includes documents and information sources developed by the International Labour Organization, the National Statistical Office of Thailand, peer-reviewed scientific publications, and master’s theses conducted in Thailand. This work is part of a needs and opportunities analysis carried out by the Center for Work, Environment, Nutrition and Development—a partnership between Mahidol University and University of Massachusetts Lowell to identify the gaps in knowledge and research to support government policy development in the area of occupational and environmental health for workers in the informal economy.